Characterization of lightweight mortars containing wood processing by-products waste. (1st October 2016) - Corinaldesi, Valeria; Mazzoli, Alida; Siddique, Rafat
Highlights: Reuse of wood waste for producing lightweight mortars. Wood mineralization through pre-soaking in calcium hydroxide aqueous solution. Laser diffraction particle size analysis & image analysis based on SEM for wood sawdust. Abstract: In this study wood processing by-products were used by replacing natural sand for producing lightweight mortars. Manufacturers of wood products and furniture generate sawdust and pieces of side-cuts from a log to rectangular shapes. These are also produced by cutting, drilling, and milling operations when a wood piece is cut either from wood logs or while preparing finished products. Saw dust is often collected in filter bags or dust collectors. Three different percentages of substitution of natural sand were tried: 2.5%, 5%, and 10% by volume of the sand. Wood by-products were always pre-soaked in water and sometimes in calcium hydroxide aqueous solution in order to obtain wood mineralization before addition to the mortar mixture. Mortars containing wood by-products were characterized by means of compression and bending tests, drying shrinkage, resistance to water vapour permeability, water capillary absorption, and thermal conductivity measurements. Results obtained showed that a maximum dosage of 5% wood by-products should be used in order to avoid an excessive loss of mortar mechanical strength, and due to the reduction of thermal conductivity of about 25%. On the other hand, if a water reducing admixture is added, adequate mechanical performance can be obtained even with 10% wood by-products.